Fluorescent Oligonucleotide Probes for Screening High-Affinity Nucleobase Surrogates - Aro-Heinila A; Lönnberg T (WILEY-V C H VERLAG GMBH, 2022)
Double-helical oligonucleotide probes featuring a single-nucleotide gap opposed by one of the canonical nucleobases and flanked by the fluorescent nucleobase analogue pyrrolocytosine have been synthesized and titrated with PdII chelates of dipicolinamide and its N-2, N-6-di-alkylated derivatives. The fluorometric titrations revealed greatly increased affinity of the PdII chelates for the nucleobases opposing the gap compared to the respective free nucleotides in solution. Owing to the constrained environment of the single-nucleotide gap, the relative stabilities of the various PdII-mediated base pairs were also significantly different from those previously reported at monomer level.